ESTUDO DE BARREIRAS TÉCNICAS NUM AMBIENTE DE PLANEJAMENTO AVANÇADO DA QUALIDADE DO PRODUTO - ENDRUWEIT, ANDREAS A. B.; SCHMIDT, AUDRIEN V.; SACKSER, GILBERTO; RIBEIRO, LUIS F. M.; DUARTE, LUIZ C. D. S.; ECKHARDT, MOACIR (Salão do Conhecimento, 2013)
Resumo